2010
DOI: 10.5697/oc.52-1.127
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, genetic, chemical and ecophysiological characterisation of two Microcystis aeruginosa isolates from the Vistula Lagoon, southern Baltic

Abstract: The motion of water due to surface waves is the most dynamic factor observed in the marine environment. In this review various aspects of the wave modelling of non-linear, steep surface waves and their role in the atmosphere-ocean interaction are discussed. Significant improvements in wave forecasting have been made in the last ten years. This is to a large extent related to substantial progress in the description of wind forcing and other processes, as well as to the more efficient use of satellite observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 103 publications
2
10
0
Order By: Relevance
“…By weight, approximately 60 % of the RM was due to Microcystis spp., with Oscillatoria and Phormidium making up the remainder. Cell sizes of Microcystis are generally small (between 2 and 8 μm in diameter) [40], while Oscillatoria and Phormidium are filamentous and form large sheets of cells that can have a wide range of sizes and are often over 100 μm [41]. A bimodal distribution in the particle size analysis would not have been expected if using a single culture or strain of cyanobacteria.…”
Section: Preparation Of Rm-bga and Physical Characterizationmentioning
confidence: 98%
“…By weight, approximately 60 % of the RM was due to Microcystis spp., with Oscillatoria and Phormidium making up the remainder. Cell sizes of Microcystis are generally small (between 2 and 8 μm in diameter) [40], while Oscillatoria and Phormidium are filamentous and form large sheets of cells that can have a wide range of sizes and are often over 100 μm [41]. A bimodal distribution in the particle size analysis would not have been expected if using a single culture or strain of cyanobacteria.…”
Section: Preparation Of Rm-bga and Physical Characterizationmentioning
confidence: 98%
“…However, it is not unknown for harmful algae to flourish in shallow waters. For instance, cyanobacteria has been known to regularly bloom in the Curonian Lagoon (Alexandrov 2010; Paldaviciene et al 2010) while Microcystis aeruginosa has also been found in water samples from the Vistula Lagoon (Mazur-Marzec et al 2010). have shown that the general reflectance characteristics of harmful algae in visible and nearinfrared spectra are similar in both turbid and open waters.…”
Section: Discussionmentioning
confidence: 99%
“…circinalis, Anabaena crassa, Aphanizomenon sp., Microcystis botrys, Microcystis wesenbergii, and Nodularia spumigena, whose occurrence could pose a serious problem in the future, due to the specific environmental conditions in the Vistula Lagoon and global warming. Mazur-Marzec et al (2010) determined the morphological, chemical, genetic, and physiological characteristics of two Microcystis aeruginosa strains isolated in the Lagoon. The obtained results validated the suitability of selected morphological traits for estimating the potential toxicity of Microcystis aeruginosa blooms.…”
Section: Studies Conducted From the Late 1970s To The Presentmentioning
confidence: 99%